The Role of Pressure and Duration of Dive on Lung Physiology in Professional and Non-Professional Divers - Jerry Indra Setiawan; Suradi Suradi; Yusup Subagio Sutanto (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Professional divers have a greater lung volume than non-professional divers in higher force vital capacity (FVC) and force expiratory flow in 1 second (FEV1) values. The purpose of this study is to analyse the effect of pressure and duration of diving on changes in lung physiology in professional divers and non-professional divers. Methods: This is a cross sectional study on the personnel of the Indonesian Navy Dislambair Koarmada II Surabaya and RSAL personnel of dr. Ramelan Navy Hospital in Lakesla Surabaya in March-April 2019. Samples was collected with purposive sampling. This study used unpaired subjects with the independent t-test statistic analysis if the data is normally distributed and the Mann-Whitney U test if the data is not normally distributed Results: There was a significant difference in the professional divers group compared to non-professional divers group in the values of FVC (P=0.042) and FEV1 (P=0.040) at 1.3 ATA for 10 minutes and the FEV1 (P=0.049) for 20 minutes. No significant differences in FVC (P=0.092) at 1.3 ATA pressure for 20 minutes. There were no significant differences in FVC (P=0.865), FEV1 (P=0.659) at 1.5 ATA pressure for 10 minutes and FVC (P=0.858) and FEV1 (P=0.857) for 20 minutes. Conclusions: The different pressure in non-professional group could reduce the FEV1 value. There was a difference in the FVC value of the professional diver group and non-professional divers at a pressure of 1.5 ATA for 10 minutes. (J Respir Indo. 2020; 40(2): 103-12)